2014
DOI: 10.1097/coh.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive and long-acting nanoformulated antiretroviral therapies for HIV-associated neurocognitive disorders

Abstract: Purpose of review This review focuses on current and future strategies to modulate neuroinflammation while reducing residual viral burden in the central nervous system (CNS). This has been realized by targeted long acting antiretroviral nano- and adjunctive therapies being developed for HIV infected people. Our ultimate goal is to eliminate virus from its CNS reservoirs and, in so doing, reverse the cognitive and motor dysfunctions seen in HIV-associated neurocognitive disorders (HAND). Recent findings Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
7
0
3
Order By: Relevance
“…Data in the literature have been mainly focused on animal infection models of nose-to-brain delivery of ketoconazole in cryptococcal meningoencephalitis [ 7 ] or on adjunctive and long-acting nanoformulated antiretroviral therapies for HIV-associated neurocognitive disorders [ 9 , 45 , 46 ], whereas data regarding bacterial infections are scarce [ 7 ]. NEs described in this study appear suitable to be administered intranasally and indicated potential benefits over other types of delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…Data in the literature have been mainly focused on animal infection models of nose-to-brain delivery of ketoconazole in cryptococcal meningoencephalitis [ 7 ] or on adjunctive and long-acting nanoformulated antiretroviral therapies for HIV-associated neurocognitive disorders [ 9 , 45 , 46 ], whereas data regarding bacterial infections are scarce [ 7 ]. NEs described in this study appear suitable to be administered intranasally and indicated potential benefits over other types of delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, nanoparticle-based delivery of doxorubicin in a rodent model of hepatocellular carcinoma was associated with significant reduction in cardiotoxicity associated with the free drug [175]. Similarly, in the last few years, antiretroviral drugs are also being formulated especially for enhanced drug delivery across blood-brain-barrier to treat HIV infection in the brain [176, 177]. CNS bioavailability of antiretroviral drugs like azidothymidine 5’-triphosphate [178] and saquinavir [179] was reported to be significantly higher following their dosing as nanoformulations.…”
Section: Development Of Das Analogs As Novel Therapeuticsmentioning
confidence: 99%
“…As such, improving ART penetration across the BBB remains an important goal. The use of nano-ART (“cell-mediated medication delivery”; reviewed in Gendelman and Gelbard, 2014 ) or the use of intranasal delivery (reviewed in Hanson and Frey, 2007 ), have shown improved efficiency in that regard. The addition to ART of adjunctive therapies targeting the excitotoxicity, inflammatory or anti-oxidant systems is also being explored.…”
Section: Neurotoxicity By Methamphetamine Use and Hiv-1 Infection: Pomentioning
confidence: 99%